Engineering mRNA-lipid nanoparticle platforms for orthopedic regenerative medicine: From formulation design to biomaterial integration - Jianan Guo; Shiyi Yao; Gen Li; Yingying Wei; Sijia Li; Renhao Yang; Hanyu Wang; Lei Wang; Huitong Ruan (Nano Research, 2026)
Abstract Messenger RNA (mRNA) therapeutics have emerged as a transformative treatment by directing in vivo therapeutic protein synthesis. Lipid nanoparticles (LNPs) currently serve as the predominant delivery vectors for mRNA. Recently, the application of mRNA-LNPs in orthopedic diseases has presented an innovative approach to musculoskeletal tissue regeneration. This review thus focuses on the pioneering design strategies and applications of mRNA-LNP in the treatment of orthopedic diseases. The review first outlines the structural compositions of LNPs, subsequently discussing design strategies for local administration of LNPs and the engineering of synergistic therapeutic platforms that integrate LNPs within functional biomaterial scaffolds, including microspheres, hydrogels, 3D-printed scaffolds, and nanofibers. Furthermore, recent advancements utilizing mRNA-LNPs to treat osteoarthritis, bone fractures, osteoporosis, rheumatoid arthritis, tendon injuries, and other orthopedic diseases are systematically summarized. This review also critically examines the current translational bottlenecks of mRNA-LNPs in orthopedic medicine and proposes future research directions.